Recent Updates in Research on Gymnema sylvestre - Jamadagni, Pallavi Shrirang; Pawar, Sharad D.; Jamadagni, Shrirang B.; Gautam, Manish; Gaidhani, Sudesh N.; Prasad, G.P.; Gurav, Arun M. (Pharmacognosy Reviews)
Gymnema sylvestrae (GS) is a large woody climbing plant that is available in dry forests of India and China. It is also proven for other activities like anti-hemolytic, anti-bacterial and anti-cancer. Present review covers recent updates in research on this plant typically during last 10 years. Also, its characterization and extraction, structure activity relationship, in-vitro pharmacology, in-vivo pharmacology, pharmacodynamics, clinical pharmacology and clinical efficacy, safety and toxicity is discussed in details. Detailed review of available literature on GS indicates it is promising plant for treatment of Type 2 Diabetes Mellitus. GS acts only in presence of pancreas as it acts by stimulation of β cells of langerhans. However, it has also shown hepatotoxic property.
Keywords: Gymnema sylvestre; Diabetes; Pharmacology; Gymnemangenin; Gymnemic acid